1981
DOI: 10.1161/01.str.12.4.454
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of focal "misery-perfusion syndrome" by extra-intracranial arterial bypass in hemodynamic cerebral ischemia. A case study with 15O positron emission tomography.

Abstract: SUMMARY Tomogrephic images of cerebral blood flow (CBF) and oxygen extraction fraction (OEF) using the U O continuous inhalation technique, and positron emission tomography, were obtained from a patient with cerebral ischemia distal to an occluded left internal carotid artery. There was a focal mismatch between CBF and oxygen metabolism in the brain supplied by tbe middle cerebral artery where CBF was decreased and OEF increased ("misery-perfusion syndrome" as opposed to "luxury-perfusioa syndrome"). These abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
296
0
7

Year Published

1983
1983
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 671 publications
(316 citation statements)
references
References 34 publications
8
296
0
7
Order By: Relevance
“…Thus, the common preoperative finding of a reduced flow in the peri-infarct areas -and the occasional finding of a focal low flow area in patients without any CT lesions whatsoever -therefore suggests, in most but not all instances, that permanent ischemic lesion has occurred. This interpretation is supported by the findings by Gibbs et al , 3 who showed that the oxygen utilization was reduced in the presence of more than adequate oxygen delivery. We have previously discussed the possible pathogenetic mechanisms to this finding, and have considered disconnection or diffuse but selective neuronal cell loss or microscopic infarcts as likely explanations.…”
Section: The Diamox Testsupporting
confidence: 71%
“…Thus, the common preoperative finding of a reduced flow in the peri-infarct areas -and the occasional finding of a focal low flow area in patients without any CT lesions whatsoever -therefore suggests, in most but not all instances, that permanent ischemic lesion has occurred. This interpretation is supported by the findings by Gibbs et al , 3 who showed that the oxygen utilization was reduced in the presence of more than adequate oxygen delivery. We have previously discussed the possible pathogenetic mechanisms to this finding, and have considered disconnection or diffuse but selective neuronal cell loss or microscopic infarcts as likely explanations.…”
Section: The Diamox Testsupporting
confidence: 71%
“…Neuronal activation imposes an increase in oxygen demand in functionally relevant brain areas, which is managed by regulatory increases in blood supply to optimize oxygen supply. 36 In the presence of cerebrovascular disease, the oxygen reserve may not be sufficient to respond to the stimulus, resulting in a loss of autoregulation. 37,38 In this situation, the standard HRF is changed and induces subsequent alterations in the BOLD signal time course.…”
Section: Discussionmentioning
confidence: 99%
“…Это можно объяснить не-однородностью изменений перфузии в полушарии на стороне окклюзии, особенно у больных с послед-ствиями завершенного ишемического инсульта. В подобных случаях регистрировались локальные зоны выраженной гипоперфузии преимущественно в области белого вещества и зонах смежного крово-обращения, которые нивелировались усиленным компенсированным кровотоком в корковых обла-стях и бассейнах передней и задней мозговых арте-рий, учитывая умеренную асимметрию полушарно-го кровотока, данная степень перфузионного дефи-цита была наиболее близка к I стадии цереброваску-лярной недостаточности по Барону [12][13][14], однако неоднородность церебральной перфузии в пределах оригинальные статьи пораженного полушария у больных с последствия-ми ишемического инсульта не позволили рассма-тривать ее как вариант компенсации мозгового кро-вотока. В частности, в области белого вещества и зон смежного кровообращения асимметрия средне-го времени транзита крови превышала 80% по срав-нению со здоровым полушарием, со снижением CBF более 40%, что соответствовало пороговым значениям области с повышенным риском развития ишемии [11,15,16].…”
Section: Discussionunclassified